Intentionally terminating life (ITL) and doctors' direct involvement (DITL). (October 2020) - George, Rob; Proffitt, Amy
Abstract: Intentionally terminating life (ITL) is usually assumed to require a doctor to perform it. However, it does not. We do not discuss this here. If ITL becomes a medical responsibility, the profession changes to incorporate a new duty to end some people's lives. This is the most significant moral question in medicine. This article intends to clarify several ethical confusions that can derail one's personal analysis. You may favour legalization of ITL without compunction, you may oppose it in any form, or you may favour ITL but see it only as safe if implemented separate from medicine. Our intention is that you engage with the moral reasoning and not the emotional polemic of this postmodern debate.